Mitochondrial NUDIX hydrolases: A metabolic link between NAD catabolism, GTP and mitochondrial dynamics. (October 2017) - Long, Aaron; Klimova, Nina; Kristian, Tibor
Abstract: NAD + catabolism and mitochondrial dynamics are important parts of normal mitochondrial function and are both reported to be disrupted in aging, neurodegenerative diseases, and acute brain injury. While both processes have been extensively studied there has been little reported on how the mechanisms of these two processes are linked. This review focuses on how downstream NAD + catabolism via NUDIX hydrolases affects mitochondrial dynamics under pathologic conditions. Additionally, several potential targets in mitochondrial dysfunction and fragmentation are discussed, including the roles of mitochondrial poly(ADP-ribose) polymerase 1(mtPARP1), AMPK, AMP, and intra-mitochondrial GTP metabolism. Mitochondrial and cytosolic NUDIX hydrolases (NUDT9α and NUDT9β) can affect mitochondrial and cellular AMP levels by hydrolyzing ADP- ribose (ADPr) and subsequently altering the levels of GTP and ATP. Poly (ADP-ribose) polymerase 1 (PARP1) is activated after DNA damage, which depletes NAD + pools and results in the PARylation of nuclear and mitochondrial proteins. In the mitochondria, ADP-ribosyl hydrolase-3 (ARH3) hydrolyzes PAR to ADPr, while NUDT9α metabolizes ADPr to AMP. Elevated AMP levels have been reported to reduce mitochondrial ATP production by inhibiting the adenine nucleotide translocase (ANT), allosterically activating AMPK by altering the cellular AMP: ATP ratio, and by depleting mitochondrial GTP pools by being phosphorylated by adenylate kinase 3 (AK3), which uses GTP as a phosphate donor. Recently, activated AMPK was reported to phosphorylate mitochondria fission factor (MFF), which increases Drp1 localization to the mitochondria and promotes mitochondrial fission. Moreover, the increased AK3 activity could deplete mitochondrial GTP pools and possibly inhibit normal activity of GTP-dependent fusion enzymes, thus altering mitochondrial dynamics. Highlights: A link between NAD + catabolism and mitochondrial dynamics is proposed. The mechanism is centered around elevated AMP due to NUDIX enzymes activity. The mechanism also supports the idea of an intra-mitochondrial PARP1. Phosphorylation of mitochondrial AMP depletes GTP levels, inhibiting fusion. Elevated AMP also activates AMPK, leading to Drp1 induced fission.